Innovation of HOTS-Based Test Instruments for Receptive Skills in Arabic Textbooks based on Kurikulum Merdeka - Elmi, Bellah Asa O'Neal; Baroroh, R. Umi; Labibah, Fitri Salwa; Azzahra, Luthfi Qolbi (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2024)
The Arabic textbook for grade VIII in SIT (Integrated Islamic  School) developed with Kurikulum Merdeka which based on HOTS learning outcomes was found that its learning assessment indicators at the MOTS assessment level. This article presents the analysis and innovation of test assessment instrument based on Higher Order Thinking Skills (HOTS) for receptive skills in the Arabic textbook Grade VIII based on Kurikulum Merdeka. A qualitative approach was applied in this research with a literature research method. Content analysis was used as the data analysis. The primary source of this research was the SIT (Integrated Islamic School) Arabic textbook by Grade VIII aligned with the Kurikulum Merdeka. Meanwhile, the secondary sources included relevant books and articles. The results of the study showed that there were 36 test assessment instruments on receptive skills (Istima’and Qira’ah). Among thirty-six test instruments, only one test instrument reached the HOTS level, while the rest were at the Middle Order Thinking Skills (MOTS) level. The proposed innovations included 11 new test instruments which cover listening (istima') and reading (qira’ah) skills. The innovation of the test instrument was based on the cognitive level of HOTS such as; analyze (C4), evaluate (C5), and create (C6). The contribution of this research was to provide a more critical test assessment instrument as the purpose of the Kurikulum Merdeka. This test instrument is expected to improve students' critical, analytical, and creative thinking skills. This HOTS-based assessment is also expected to be a feedback for teachers in improving the quality of learning.